New records of Phacus and monomorphina taxa (Euglenophyta) for Thailand - Kritsana Duangjan (2018)
© by Kritsana Duangjan 2015. The diversity of Phacus and Monomorphina (Euglenophyta) from northern Thailand was studied in various water bodies of Chiang Mai, Chiang Rai, Lamphun, Lampang and Phayao provinces. This paper presents 25 taxa of Phacus and 1 Monomorphina new for Thailand, including 3 Phacus taxa new for Southeast Asia. Several varieties and forms were recognized. All are briefly described, with original illustrations.